EFFECTIVENESS OF THE WHEAT Lr22b, Lr34, AND Lr37 GENES FOR ADULT PLANT RESISTANCE TO LEAF RUST IN WEST SIBERIA AND THE CYTOPHYSIOLOGICAL BASIS OF THEIR ACTION - L. Ya. Plotnikova (Vavilovskij Žurnal Genetiki i Selekcii, 2014)
The effect of genes for adult plant resistance to leaf rust has been explored in southern West Siberia by the examples of common wheat cv. Thatcher (Tc), carrying the Lr22b gene, and its near-isogenic lines TcLr34 and TcLr37. Lr22b is ineffi cient, Lr34 slows down the disease development at a mean daily temperature below 16 ºС, but is poorly efficient at temperatures above 20 ºС. Lr37 confers high resistance under all conditions. At the heading stage, TcLr34 and TcLr37 show similar components of partial resistance to rust: reduction in the number and sizes of spots and sporogenesis suppression. Cytological examination has revealed partial suppression of the formation of Puccinia triticina infection signs (appressoria and haustorium) without hypersensitive reaction (HR). Additional defense mechanisms include an oxidative burst induced by contacts of appressoria with stomata and callose-lignine appositions on the wall. Auto fluorescence of lignins in TcLr34 and TcLr37 lines differs from the glow typical of HR-accompanied combinations. The Lr34 and Lr37 genes exert a pleiotropic action on pathogenesis.